PENETAPAN KADAR FLAVONOID TOTAL EKSTRAK ETANOL KULIT BATANG SAWO (Manilkara zapota (L.)) SECARA SPEKTROFOTOMETRI UV-VISIBEL - Ratna Widyasari; Dina Yuspita Sari (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Sawo (Manilkara zapota (L.)) is one of the plants that can be used in traditional medicine. Sawo bark contains secondary metabolites of flavonoids, saponins, tannins, and phenolics. This study aims to determine the total flavonoid content in the ethanol extract of sapodilla stem bark. Determination of total flavonoid content using a colorimetric method using AlCl3 reagent. Determination of total flavonoid using UV Visible Spectrophotometry at a maximum wavelength of 417.50 nm and total flavonoid expressed in QE (Quercetin Equivalent).. The results showed that the total flavonoid content contained in the ethanol extract of the Sawo Bark (Manilkara zapota (L.)) was 1,095 mgQE/g.